Total Breast Reconstruction With Fat Grafting After Internal Expansion and Expander Removal. Issue 4 (April 2017) - Manconi, Andrea; De Lorenzi, Francesca; Chahuan, Badir; Berrino, Valeria; Berrino, Pietro; Zucca-Matthes, Gustavo; Petit, Jean Yves; Rietjens, Mario
Abstract : Introduction: The development of fat grafting techniques both in cosmetic and reconstructive breast surgery has highlighted the need to recreate a breast mound using similar tissues and without visible scarring. Our technique combines skin expansion by conventional expanders and breast volume replacement by serial fat grafting and final expander removal. Materials and methods: Fat grafting had been performed both by Coleman technique and Bodyjet system. We report a series of 12 cases enrolled between 2008 and 2013. Each case has been presented in this article, focusing on received treatment, observed complications, and results. Results: Satisfactory results were observed 6 months after the last session in most of the concluded reconstructions with a low complication rate.